Optical Properties of Polymers Under Gamma Irradiation: A Systematic Review 2020–2025 - Sithivinayagam, Sithivinayagam; Vincent, Sofia; Pattanaik, Ashutosh; Krishnan, Kumar (Universitas Pendidikan Mandalika, 2026)
Gamma irradiation is widely applied in polymer processing, sterilization, and radiation resistance testing, yet its optical consequences are interpreted inconsistently across applications. This systematic literature review synthesizes Scopus indexed experimental studies published between 2020 and 2025 to clarify how gamma exposure modifies polymer optical properties and how interpretation depends on material architecture and analytical approach. Following PRISMA procedures, 657 records were identified, 76 full texts were assessed, and 24 studies met predefined eligibility criteria. The included corpus is dominated by PVA based composites and functional films, with fewer studies on neat engineering polymers and multilayer packaging systems. Across studies, UV–Vis spectral changes and visible color modification are the most frequently reported outcomes. In dosimetry oriented systems, absorbance and color intensity commonly increase with dose and support calibrated optical readout. In stability focused systems, especially EVA based materials, optical constants such as refractive index often remain largely unchanged within moderate dose windows. Optical band gap Eg, when reported, is frequently described as decreasing with increasing dose in composite and doped films, although its magnitude depends on transition assumptions and fitting procedures. Overall, optical response under gamma irradiation is material and context dependent, and changes may indicate either functional responsiveness or degradation, requiring endpoint aware interpretation and more standardized reporting practices.